2017
DOI: 10.6001/actamedica.v24i3.3549
|View full text |Cite
|
Sign up to set email alerts
|

Severity of hyperoxia as a risk factor in patients undergoing on-pump cardiac surgery

Abstract: Background.Hyperoxia has long been perceived as a desirable or at least an inevitable part of cardiopulmonary bypass. Recent evidence suggest that it might have multiple detrimental effects on patient homeostasis. The aim of the study was to identify the determinants of supra-physiological values of partial oxygen pressure during on-pump cardiac surgery and to assess the impact of hyperoxia on clinical outcomes.Materials and methods.Retrospective data analysis of the institutional research database was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“… 32 In a study by Sutton et al 33 conducted on cardiac surgery patients, an increase in both ICU and hospital stays was observed in hyperoxemic patients. Similar to our study, in a study by Jakutis et al, 16 while the duration of ICU stay was not affected by hyperoxemia, the length of hospital stay was prolonged. In our study, the length of stay in the ICU was not affected despite the prolongation of the MV period with the routine postoperative ICU stay of at least 36 hours in the cardiac surgery protocols applied in our clinic.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 32 In a study by Sutton et al 33 conducted on cardiac surgery patients, an increase in both ICU and hospital stays was observed in hyperoxemic patients. Similar to our study, in a study by Jakutis et al, 16 while the duration of ICU stay was not affected by hyperoxemia, the length of hospital stay was prolonged. In our study, the length of stay in the ICU was not affected despite the prolongation of the MV period with the routine postoperative ICU stay of at least 36 hours in the cardiac surgery protocols applied in our clinic.…”
Section: Discussionsupporting
confidence: 92%
“… 15 It was observed that liberal oxygen therapy (PO 2 =190–300 mmHg) was associated with prolonged MV duration compared with conservative oxygen therapy (PO 2 =75–112 mmHg). 16 In a more recent study, Jakutis et al 16 showed that the duration of MV was longer in patients with severe hyperoxemia (PO 2 >300 mmHg) during CPB. Various studies have also indicated that hypoxemia affects the duration of MV in cardiac surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Oxygen, whilst vital, can also be toxic, with both oxidative stress and cellular hyperoxia identified as major contributors to multiple pathological states (Evans, 2016). Historically, under-oxygenation was (and still remains) the key concern in patients undergoing cardiac surgery, although recent studies are starting to highlight the pathological dangers of over-oxygenation during CPB, with an ongoing debate around the level of damage (Jakutis et al, 2017; Young 2012; Abou-Arab et al, 2020). Equally, being able to define what these terms (over- and under-oxygenation) mean is complex.…”
Section: Physiological Interpretation Of Findingsmentioning
confidence: 99%
“…However, recent reports have described a potential association of hyperoxia with poor outcomes in select critical care populations (6)(7)(8)(9)(10)(11)(12), and the balance of benefits and risks of hyperoxia in patients undergoing CPB remains unknown (1,13). Oxidative stress from the generation of reactive oxygen species, hyperoxiarelated cardiovascular dysregulation, and inflammation and thrombosis from activation of neutrophils and platelets favor limiting the utilization of hyperoxia (1,(13)(14)(15)(16)(17). Additionally, high partial pressures of oxygen may be associated with an increase in systemic and coronary vascular resistance (1,(17)(18)(19) which impairs cardiac diastolic function (1,20).…”
mentioning
confidence: 99%